2020
DOI: 10.1111/echo.14641
|View full text |Cite
|
Sign up to set email alerts
|

Focused cardiac ultrasound training in medical students: Using an independent, simulator‐based curriculum to objectively measure skill acquisition and learning curve

Abstract: Background Using simulators built and validated at the University of Washington (UW), the study sought to test whether medical students can learn the basic skills of focused cardiac ultrasound (FoCUS) from an individually paced, simulator‐based curriculum, how skills improve, and the rate at which these skills are acquired. Methods The curriculum presented didactic material interspersed with hands‐on practice. Psychomotor skill was measured by the angle error of the acquired image view plane relative to the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 21 publications
0
19
0
5
Order By: Relevance
“…Previous work has also shown that novices with no POCUS experience can rapidly learn POCUS image acquisition skills for both lung and cardiac POCUS. 23,24 These findings support the continued development of programs to train prehospital providers in POCUS when early diagnosis can have a major impact on patient outcomes. 11 Few novices reached the HMA metrics obtained by POCUS experts, despite the fact that most were deemed competent in image acquisition with the OSCE.…”
Section: Discussionmentioning
confidence: 67%
“…Previous work has also shown that novices with no POCUS experience can rapidly learn POCUS image acquisition skills for both lung and cardiac POCUS. 23,24 These findings support the continued development of programs to train prehospital providers in POCUS when early diagnosis can have a major impact on patient outcomes. 11 Few novices reached the HMA metrics obtained by POCUS experts, despite the fact that most were deemed competent in image acquisition with the OSCE.…”
Section: Discussionmentioning
confidence: 67%
“…O que se sabe é que um currículo baseado em simulador melhora as habilidades do estudante de medicina de forma objetiva e quantificável. 28 Apesar das diferentes formas de ensino, a integração da disciplina de US no currículo gera feedbacks positivos por parte dos acadêmicos. Houve um estudo em que a totalidade dos participantes concordava ou concordava fortemente em adquirir certificação formal em US do trauma após a conclusão do curso.…”
Section: Discussionunclassified
“…A recent Denmark national needs assessment study for prioritizing procedures for a stimulation‐based cardiology curriculum showed that TEE came in second only to advanced life support 18,19 . Many recent studies have demonstrated the effectiveness of simulator‐based training for improving the ability of novice operators to achieve proficiency in echocardiography 20–26 …”
Section: Discussionmentioning
confidence: 99%